Factors Influencing Insulin Absorption Around Exercise in Type 1 Diabetes - Pitt, Jason P.; McCarthy, Olivia M.; Hoeg-Jensen, Thomas; Wellman, Benjamin M.; Bracken, Richard M. (Frontiers in Endocrinology, 2020)
International charities and healthcare organisations advocate regular physical activity for health benefit in people with type 1 diabetes. Clinical expert and international diabetes organisations’ position statements support the management of good glycaemia during acute physical exercise by adjusting exogenous insulin and/or carbohydrate intake. Yet research has detailed, and patients frequently report, variable blood glucose responses following both the same physical exercise session and insulin to carbohydrate alteration. One important source of this variability is insulin delivery to the circulation. With modern insulin analogues, it is important to understand how different insulins, their delivery methods, and inherent physiological factors, influence the reproducibility of insulin absorption from the injection site into circulation. Furthermore, contrary to the adaptive pancreatic response to exercise in the person without diabetes, the physiological and metabolic shifts with exercise may increase circulating insulin concentrations that may contribute to exercise-related hyperinsulinaemia and consequent hypoglycaemia. Thus, a furthered understanding of factors underpinning insulin delivery may offer more confidence for healthcare professionals and patients when looking to improve management of glycaemia around exercise.